A reverse Mulholland-type inequality in the whole plane - Jianquan Liao; Bicheng Yang (Journal of Inequalities and Applications, 2018)
Abstract We present a new reverse Mulholland-type inequality in the whole plane with a best possible constant factor by introducing multiparameters, applying weight coefficients, and using the Hermite–Hadamard inequality. Moreover, we consider equivalent forms and some particular cases.